Earth at Risk in the 21st Century: Rethinking Peace, Environment, Gender, and Human, Water, Health, Food, Energy Security, and Migration - Oswald Spring, Úrsula. author. aut Link
XLVII, 641 p. 101 illus., 89 illus. in color.
Keywords: Earth at Risk in the 21st Century offers critical interdisciplinary reflections on peace, security, gender relations, migration and the environment, all of which are threatened by climate change, with women and children affected most. Deep-rooted gender discrimination is also a result of the destructive exploitation of natural resources and the pollution of soils, water, biota and air. In the Anthropocene, the management of human society and global resources has become unsustainable and has created multiple conflicts by increasing survival threats primarily for poor people in the Global South. Alternative approaches to peace and security, focusing from bottom-up on an engendered peace with sustainability, may help society and the environment to be managed in the highly fragile natural conditions of a ‘hothouse Earth’. Thus, the book explores systemic alternatives based on indigenous wisdom, gift economy and the economy of solidarity, in which an alternative cosmovision fosters mutual care between humankind and nature. • Special analysis of risks to the survival of humankind in the 21st century. • Interdisciplinary studies on peace, security, gender and environment related to global environmental and climate change. • Critical reflections on gender relations, peace, security, migration and the environment • Systematic analysis of food, water, health, energy security and its nexus. • Alternative proposals from the Global South with indigenous wisdom for saving Mother Earth.